Review of Chaisemartin, N.; Theodorescu, D. Le théâtre d’Aphrodisias : les structures scéniques. Aphrodisias 8 (2017) (Revista Archai, 2020)
Review of Chaisemartin, N.; Theodorescu, D. Le théâtre d’Aphrodisias : les structures scéniques. Aphrodisias 8 (2017)